L’azione pubblicistica di adempimento nell’ordinamento giuridico italiano - Tocci, Mario (Civil Procedure Review, 2018)
The article intends to analyse the Italian legal action to ensure the fulfilment of the obligations of public authorities. This commitment action, regarding a remedy of specific performance actually provided in the Code of the Administrative Process (Legislative Decree No 104/2010), cannot be brought autonomously because it has to be accompanied by another main action for annulment.